Design and Simulation of a 200 MWp Floating Solar PV Plant Integrated with the Kainji Hydropower Plant, Nigeria - ADAMU, Umar A.; HARUNA, Ya’u S.; BAKARE, Ganiyu A.; MAMMAN, Buhari H.; MUSTAPHA, Kunduli; ADAMU, Hadi M.; MAHMUD, Ismaila (FUDMA Journal of Engineering and Technology, 2026)
Nigeria continues to experience persistent electricity generation deficits despite its abundant renewable energy resources. This study presents the design and simulation of a 200 MWp Floating Solar Photovoltaic (FSPV) plant integrated with the 760 MW Kainji Hydropower Plant as a hybrid renewable energy solution for improving grid reliability and renewable energy penetration. Meteorological, hydrological, and geographical data of the Kainji reservoir were analysed. PV system sizing and energy yield simulations were carried out using PVsyst, while floating platform structures, pontoons, anchors, and mooring systems were modelled using SketchUp. The results showed that the system required 333,340 monocrystalline PV modules rated at 600 W each, installed at an optimal tilt angle of 12°, supported by approximately 4.0 million pontoons (12 pontoons per module), occupying about 1.01 km² of reservoir surface area—only 2.7% of the feasible reservoir area. The proposed plant achieves an annual energy yield of approximately 322.1 GWh at P50 (i.e., 50 % probability of exceedance), with a performance ratio of 77.97% and a capacity factor of 18%. The hybrid configuration leveraged the existing 330 kV transmission infrastructure and allowed hydropower to act as virtual energy storage, improving dispatch flexibility and grid stability. The study confirms the technical feasibility of large-scale FSPV deployment in Nigeria and provides a practical framework for integrating floating solar with existing hydropower assets.
Keywords: Floating Solar Photovoltaic, Hybrid Renewable Energy System, Kainji Dam, PVsyst, Grid Stability.